Using Peer Support to Reduce Fault-Tolerant Overhead in Distributed Shared Memories - Hunt, Galen; Scott, Michael L. (1996)
Introduction of a peer logging system for reducing performance overhead in fault-tolerant distributed shared memory systems. This system provides fault-tolerant shared memory using individual checkpointing and rollback.